(untitled) (Theatrum historiae, 2018)
Heinrich von Wildenstein is known to have preached at the funeral of Charles IV in 1378, but there was no biographical study of this preacher until now. The paper focuses on portraying a life of the cleric, who maintained close contact with the papal curia in Avignon and Rome, who held three episcopal offices during his lifetime (in Krujä, Trieste and Pićan), and he also stayed in Bohemia in the 1370s. He is documented to have resided at the court of emperor Charles IV in Prague, as well as at the court of bishop Albert von Sternberg in East Bohemian town Litomyšl. The paper also tries to clarify a question of Heinrich‘s origin.